Formulation And Evaluation of Oral Micelles Carriers for Solubility Enhancement - Soni, Kirti; Jain, Rakhee Kapadia (Journal of Neonatal Surgery, 2025)
In the present study, oral micelles with a hydrophilic polymer and surfactant were developed using the hot homogenization technique process to improve the dissolution. The physicochemical properties of the lovastatin containing oral micelles were characterized using scanning electron microscopy, differential scanning calorimetry, powder X-ray diffraction, and a particle-size analyzer. The mean particle size of all Oral Micelles that were prepared was less than 500 nm. Polyethylene glycol (PEG) oral micelles significantly increased the maximum dissolution when compared with propylene glycol (PG), and polyvinylpyrrolidone (PVP) oral micelles. In this study, the oral micelles with a LO:PC:LC; 2:1:1.5 have rapid dissolution within 30 minutes, in addition to good oral bioavailability, with These results suggest that the preparation of lovastatin oral micelles using the hot homogenization process is a promising approach to improve the dissolution and absorption properties of drug.